Healthy mind, healthy body: A randomized trial testing the efficacy of a computer-tailored vs. interactive web-based intervention for increasing physical activity and reducing depressive symptoms - Rebar, Amanda; Boles, C.; Burton, N.; Duncan, M.; Short, C.; Happell, B.; Kolt, G.; Caperchione, C.; Rosenkranz, R.; Vandelanotte, C. (Elsevier BV, 2016)
© 2016 Elsevier Ltd Physical activity is an effective primary or adjunctive treatment to reduce depressive symptoms. Computer-tailored and interactive web-based physical activity interventions are potentially effective and accessible means for promoting physical activity, but little evidence exists regarding their efficacy in reducing depressive symptoms. We conducted a 2-arm randomised trial to compare the efficacy of these web-based interventions for increasing physical activity and reducing depressive symptoms. Participants (18 years or older and had no health condition limiting physical activity) were randomised to have access to a web-based physical activity intervention program with either computer-tailored advice (MyPAA) or interactive features (Walk 2.0). Only half of participants accessed the website at least once (MyPAA: allocated n = 252, accessed program n = 154, 61.1%; Walk 2.0: allocated n = 262, accessed program n = 120, 45.8%). Participants and the research team were blinded to group assignment. There were no significant between-group differences in change of self-reported physical activity or depressive symptoms. Physical activity significantly increased from baseline to one month (g = 0.21) and three months (g = 0.20), and depressive symptoms significantly decreased from baseline to one month (g = 0.36) and three months (g = 0.42). People who visited the website more and for longer had larger changes in physical activity and depressive symptoms than those who visited less. Web-based interventions with computer-tailoring and interactive features show promise as a method for increasing physical activity and reducing depressive symptoms, particularly for those who engage with the program. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12613001215718.